An Insight on the Prospects of Biofloc Technology (BFT) in the North-Eastern States of India - Singh, Moirangthem Kameshwor; Boruah, Dipjyoti (Asian Journal of Biological and Life Sciences)
Aquaculture farming is presently facing challenges in terms of effluent discharge it releases into the natural environment. Farmers opt for intensive culture methods for high production which results in deteriorated water quality of the surrounding habitat and introduces pathogen, leading to disease outbreak. The north-eastern region of India is one of the hotspots of freshwater fish biodiversity in the world with apprx. 300 fish species belongings to 10 different orders, 37 families and 114 genuses. The region covers largest part of the Eastern Himalayan ranges. Topographically hilly regions are resource poor for aquaculture in terms of land and water and most of the land areas are also flood prone. Thus it caused the need of a sustainable aquaculture technology. This article focuses on an advanced technology, called Biofloc technology based on zero water exchange and wastes recycling produced inside the cultured system by utilizing the mixture of bacteria, algae, detritus forming the microbial floc. The water quality remains maintained due to the conversion of the toxic nitrogenous wastes of the cultured species into proteinaceous diet which can be eventually consumed by the cultured species itself, thus replacing the high cost fish feed available in the market. This novel technology proves to be a cost effective as it utilizes fewer resources in terms of water, space, energy and eventually capital with a low operating and management cost. The north-eastern states of India can adapt this technology for a high yield in fish production and to boost up the rural economy, employment generation and also to conserve the valuable species of the region.
Keywords: Biofloc technology; Northeast India.; Nutrient cycling; Nutritious microbial cells; Sustainable aquaculture; Zero water exchange